THE INFLUENCE OF CAREER CHOICE MOTIVATION ON STUDENT’S PROFESSIONAL ORIENTATION AND DEVELOPMENT - Purevsuren Gendensuren; Octyabrijargal Enkhee (International Journal of Innovative Technologies in Social Science, 2025)
Since the early 19th century, research on motivation has been extensive. American psychologists A. Maslow and V. Frankl explored motivation in relation to needs, leading to ongoing experimental research. From 1980 onwards, motivation became a distinct subject of experimental inquiry, reflecting human reality by guiding behaviors and actions. Researchers have focused on motivation in connection with needs, emphasizing individuals’ intrinsic readiness to engage actively in specific areas. Needs drive human activities and behavior, determining orientation and actions. Human motivation is diverse, influenced by factors like needs, desires, passions, and interests, with actions often driven by multiple motives. Choosing a profession involves interests, talents, psychology, physical development, and social attitudes, determining one’s role in society and life path. To make an informed decision, individuals must assess their talents, knowledge, and opportunities, selecting a profession that aligns with their personal characteristics and qualities for productive study and performance. In today’s society, young people often prioritize professions based on reputation and prestigious schools, influenced by the desire to please others. University enrollment typically includes individuals aged 16-20, navigating self-discovery as they solidify their self-image and focus on academic and professional pursuits for independent life. Motivation is crucial in profession selection, requiring a deep understanding of the profession’s attributes. Positive or intrinsic motivation drives students to engage creatively in learning tasks, work with determination, and maintain a favorable outlook, enhancing professional orientation and interest. In modern social and economic development, the demand for specialists and expectations are constantly evolving. University training plays a vital role in shaping professional orientation, explored in disciplines like anthropology, philosophy, sociology, pedagogy, and psychology. Adolescence is a critical stage for choosing a career path, necessitating exploration of the psychological and social factors influencing decision-making.